Stochastic Dynamic Program For Optimization Analysis Of Nglambangan Reservoir - Indriani, Yulia; Mushthofa, Mushthofa; Wicaksono, Bayu (Electronic Journal of Education, Social Economics and Technology, 2025)
The study addresses water management issues at the research site, including dry-season water shortages, increasing irrigation demands due to population growth, and inefficient reservoir use. Reservoir operation is modeled as a multi-stage problem, with each period representing a stage, active storage as the state variable, and inflow discharge—stochastic by nature—as input data. A stochastic dynamic programming (SDP) approach is applied to optimize reservoir operations by accounting for hydrological variability and uncertainty. The stochastic model defines discrete possibilities of reservoir storage at each stage, each associated with a probability. The optimization results show that with a water allocation of 1,750,000 m³ for MT I and 750,000 m³ for MT II, a profit of Rp. 40.34 billion was achieved. To explore more optimal results, further allocation scenario analyses are recommended.